Scaling of structural strength - Bazant, Z. P.
Exemplifying the relationship between experimental research, material modeling, structural analysis and design, this book focuses on the effect of structure size on structural strength and failure behaviour. It also discusses Bazant's theory, which has found wide application to all quasi-brittle materials.